Fiscal Challenges of Population Aging in Brazil - Cuevas, Alfredo (IMF Working Papers; Working Paper ;, 2017)
In recent decades, population has been aging fast in Brazil while old age pensions and healthrelated spending have increased. As the population ages, the spending trend threaten to reach unsustainable levels absent reforms. Increasing the retirement age is key, but by itself will not provide sufficient savings to close the pension system financing gap, and reforms reducing replacement rates are necessary. In the area of health, there is scope for improving expenditure efficiency by strengthening outpatient care and regional networks, and developing clinical guidelines for cost-effective treatments and drugs. Reforms are urgent, so that they can be gradual.